A cultural discourse analysis of obituaries in China. Issue 3 (3rd July 2018) - Chang, Yanrong (Yvonne)
ABSTRACT: Discourse enacts and creates cultural meanings and it can be used by powerless cultural members to creatively and rhetorically assert self-worth and have their voices heard. Taking a cultural approach to discourse and communication, this study examined three types of obituary discourse in the Chinese society. It shows that multiple obituary discourses enact and discursively create a stratified society. It also demonstrates the liberating power of the obituary discourse in giving voice to the powerless.